The Durability of Fiber–Plastic Composite with Maleic Anhydride (MAH) as Compabilitizer and Benzoyl Peroxide (BPO) as Initiator toward Termits Attack - Pandapotan Christian Purba; Luthfi Hakim; Ridwanti Batubara (Peronema Forestry Science Journal, 2014)
The use of plastic fiber composite (FPC) for exterior purposes as one alternative to solid wood has a variety of power requirement one of which is resistant to termites. This study aimed to test the durability of fiber composite plastic derived from recycled corrugated old paper fibers and polypropylene (PP) with the addition of maleic andhirida (MAH) as compabilitizer and benzoyl peroxide (BPO) to termite attack. This research used Completely Randomized Design (CRD) factorial, there are two factors: comparison of corrugated old paper fibers and polypropylene (PP), which consists of 50:50, 60:40 and 70:30 and additive factors maleit anhirida (MAH) 1% and 2% and the results were compared with JIS A 5905-2003 S20 hardboard and JIS A 5908-2003 particleboards type 13 for physical properties and SNI 01 7202-2006 to test the grave yard test termites. The results showed after trials testing the grave for 100 days, the physical properties of the fiber composite plastic does not entirely meet the testing standards JIS A 5905-2003 S20 hardboard and JIS A 5908-2003 particleboards type 13. To test resistance to termite attack, some fiber plastic composite that meets the ISO standard FPC 50:50 01 7202-2006 1% MAH, 1% MAH 60:40, 60:40 and 70:30 2% MAH while the remaining 2% are outside the standard. The Patterns of termite attack on FPC 50:50 70:30 2% and 1% MAH MAH resembles a circular pattern.Keywords : corrugated old paper fiber, polypropilene, fiber plastic composite, durability against termite attack.